Reporting of Economic Subject in the Kazakhstan Press (Herald of Journalism, 2022)
This article deals with the attention to features and giving methods of economic subjects in Ka- zakhstan’s periodicals. At the moment in the press the economic subject became separate on business journalism and economic journalism. Moreover, there were editions which are completely devoted to economy. Together with it, they have impact to policy and authority. The economic subject works for the benefit of all structures of society.Speaking about business journalism we report news about the changes happening in business at the enterprises and in economy. Problem of business journalism not only provide with information society, but also to introduce new technologies, to form the correct understanding concerning production and finance. Objectively, each economic publishing house reports the opinion of changes in economy, on their shortcomings and advantages. This subject in Kazakhstan is still a little studied. In our work the comparative analysis of giving of economic news in Kazakh and Russian languages is given.The two types of journalism in Kazakhstan today are: in Kazakh language and in Russian. The ten- dency to report about intervention of the state in trade was outlined in Russian-speaking journalism, thus imposing to the reader the ideas.In the economic press of Kazakhstan some ill-defined articles are written not with journalists, but economists. And many thematic editions don’t correspond to the status. And if correspond, can’t give rather objective view. In most cases it is simple reporting of information.Key words: Press, economy, business journalism, business journalism, article.